2011
DOI: 10.1161/strokeaha.110.600312
|View full text |Cite
|
Sign up to set email alerts
|

Beta 2 Microglobulin and the Risk for Cardiovascular Events in Patients With Asymptomatic Carotid Atherosclerosis

Abstract: Background and Purpose-Atherosclerosis is a chronic inflammatory disease. Ongoing inflammation is associated with elevated levels of beta 2 microglobulin (B2M). We investigated B2M levels in a large cohort of patients with carotid atherosclerosis for the occurrence of major adverse cardiovascular events. Methods-One thousand five of 1286 consecutive, neurologically asymptomatic patients with carotid atherosclerosis were followed for a median of 3 years (interquartile range, 2.5 to 3.5) for the occurrence of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
65
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 31 publications
4
65
0
1
Order By: Relevance
“…However, changes in early kidney biomarkers, such as Cys-C in non-kidney diseases, have been associated with an increased rate of mortality from both CVD and non-CVD (pulmonary diseases, cancer, infections), as indicated by the quartiles of kidney function [47]. On the other hand, β2M, also used as an early kidney biomarker, has been reported to be independently associated with the mortality from heart attacks and strokes in patients with asymptomatic coronary atherosclerosis [48]. …”
Section: Discussionmentioning
confidence: 99%
“…However, changes in early kidney biomarkers, such as Cys-C in non-kidney diseases, have been associated with an increased rate of mortality from both CVD and non-CVD (pulmonary diseases, cancer, infections), as indicated by the quartiles of kidney function [47]. On the other hand, β2M, also used as an early kidney biomarker, has been reported to be independently associated with the mortality from heart attacks and strokes in patients with asymptomatic coronary atherosclerosis [48]. …”
Section: Discussionmentioning
confidence: 99%
“…B2M is a polypeptide forming a small subunit of the major histocompatibility class I molecule on the surface of nucleated human cells and thrombocytes and is eliminated by the kidney. 9, 29 A few studies have reported a significant prospective association between B2M and CVD, 29, 30 but the mechanisms by which B2M confers CVD risk is not well understood. B2M may merely be a good marker for kidney dysfunction, 31 but, some investigators have suggested non-kidney pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective cohort study of nondisabled people 65 years and older, Β2M concentrations better predicted death than high sensitivity C-reactive protein (CRP), an established inflammatory marker (1). In addition, several cohort studies, including the Atherosclerosis Risk in Communities Study (ARIC) (7), have reported positive associations between Β2M and aging, various cardiovascular conditions, and mortality from diabetes, CVD and all causes, suggesting that serum B2M may also serve as an inflammatory biomarker (7, 17, 18). …”
Section: Introductionmentioning
confidence: 99%